Răspuns :
Răspuns:
- x = 0,75
Explicație pas cu pas:
(1,2+3,2 · (3x + 0,75)]: 3 = 3,6
(1,2 + 3,2 · (3x + 0,75) = 3,6 · 3
1,2 + 3,2 · (3x + 0,75) = 10,8
3,2 · (3x + 0,75) = 10,8 - 1,2
3,2 · (3x + 0,75) = 9,6
3x + 0,75 = 9,6 : 3,2
3x + 0,75 = 3
3x = 3 - 0,75
3x = 2,25
x = 2,25 : 3
x = 0,75
#copaceibrainly
[1,2+3,2*(3x+0,75)]:3=3,6
[1,2 + 3,2*(3x + 0,75)] = 3,6*3 =10,8
3,2*(3x + 0,75) = 10,8 - 1,2 = 9,6
3x + 0,75 = 9,6:3,2 = 3
3x = 3 - 0,75 = 2,25
x = 2,25 : 3 = 0,75
✅Sper ca este bine!✅
[1,2 + 3,2*(3x + 0,75)] = 3,6*3 =10,8
3,2*(3x + 0,75) = 10,8 - 1,2 = 9,6
3x + 0,75 = 9,6:3,2 = 3
3x = 3 - 0,75 = 2,25
x = 2,25 : 3 = 0,75
✅Sper ca este bine!✅